2013
DOI: 10.1021/ic3024716
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Ordering in Tetragonal 3d Metal Arsenides M2As (M = Cr, Mn, Fe): An Ab Initio Investigation

Abstract: The electronic and magnetic structures of the tetragonal Cu 2 Sb-type 3d metal arsenides (M 2 As, M = Cr, Mn, Fe) were examined using density functional theory to identify chemical influences on their respective patterns of magnetic order. Each compound adopts a different antiferromagnetic (AFM) ordering of local moments associated with the 3d metal sites, but every one involves a doubled crystallographic c-axis. These AFM ordering patterns are rationalized by the results of VASP calculations on several magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 52 publications
(101 reference statements)
5
33
0
Order By: Relevance
“…The similarity of these orderings, as well as the robustness with respect to U of their energetic closeness, suggest that these antiferromagnetic orderings are likely to coexist within the CrMnAs crystal structure at finite temperatures. It is suggestive that the same four magnetic orderings were previously found to be energetically competitive in Cr 2 As[9].The coloring I non-spin-polarized density of states shows a pseudogap at the Fermi energy for U from 1 eV to 3 eV, which is consistent with the values of U that have proven to be useful in manganese oxides. U is an empirical parameter, and similar values of U should not necessarily be optimal for different systems.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…The similarity of these orderings, as well as the robustness with respect to U of their energetic closeness, suggest that these antiferromagnetic orderings are likely to coexist within the CrMnAs crystal structure at finite temperatures. It is suggestive that the same four magnetic orderings were previously found to be energetically competitive in Cr 2 As[9].The coloring I non-spin-polarized density of states shows a pseudogap at the Fermi energy for U from 1 eV to 3 eV, which is consistent with the values of U that have proven to be useful in manganese oxides. U is an empirical parameter, and similar values of U should not necessarily be optimal for different systems.…”
supporting
confidence: 83%
“…Therefore, the DFT + U method with empirically fitted values of U is often useful for examining the electronic structures of highly correlated electron systems such as those containing rare-earth metals. In a previous computational study on 3d dimetal arsenides by Zhang et al, including a Hubbard U term resulted in better agreement between calculated and experimental magnetic moments for Mn 2 As than were obtained by DFT alone [9]. In manganese oxides, the DFT+U method has proven superior to DFT alone in calculating oxidation [53].…”
Section: Vaspmentioning
confidence: 95%
See 1 more Smart Citation
“…The values of effective U parameters for Mn used in these studies ranged from 1.6 eV to 4 eV . A previous computational study on 3 d di‐metal arsenides by Zhang et al showed that including a Hubbard U ‐term with a value ranging from 1 to 4 eV for Mn in Mn 2 As resulted in better agreement between calculated and experimental local magnetic moments. Also in this study the calculated magnetic ground state switched from antiferromagnetic (the experimentally determined ground state) to ferrimagnetic for U values between 0.5 eV and 2 eV, but then returned to antiferromagnetic for values of U above 2 eV, results which indicate significant sensitivity to the ground state magnetic ordering and the U parameter assigned to Mn.…”
Section: Introductionmentioning
confidence: 98%
“…According to these diagrams, the direct M1M1 and M1M2 interactions of CrMnAs resemble those of Cr 2 As and not Mn 2 As, whereas the nearest‐neighbor M2M2 interactions resemble those of Mn 2 As and not Cr 2 As. As a result, the indirect M2M2 exchange interactions across the M1 planes are antiferromagnetic in CrMnAs, as in Cr 2 As but not in Mn 2 As.…”
Section: Introductionmentioning
confidence: 99%